Pneumatic versus hydrostatic reduction in the treatment of intussusception in children. Issue 4 (October 2017) - Ali, Ahmad; Sheir, Hesham; Saied, Basem; Wafa, Tamer; El-Ghazaly, Mohamed
Abstract : Background: The aim of this study was to compare pneumatic reduction under guidance of fluoroscopy and hydrostatic saline enema reduction under guidance of ultrasound in treatment of intussusception in pediatric patients. Methods: The study included 80 patients with intussusception in the time period from September 2014 to September 2015 who were divided into two groups: group A included 40 patients who underwent US guided hydrostatic reduction and group B included 40 patients who underwent fluoroscopic guided pneumatic reduction. Results: The success rate was significantly higher in the pneumatic group (80%) ( P =0.017) when compared to the hydrostatic group (55%) after 1st trial. However, the outcome was equal in both groups after the 2nd trial with success rate of 82.5%. The time needed for reduction was significantly shorter in the pneumaic group ( P =0.001). There was only one case of perforation in hydrostatic group (2.5%). Conclusion: Pneumatic reduction is safe, simple, fast, less messy and as effective as hydrostatic reduction.